BASALTIC THERMALS AND SUBPLINIAN PLUMES: CONSTRAINTS FROM ACOUSTIC MEASUREMENTS AT SHISHALDIN VOLCANO, ALASKA - Vergniolle S.; Caplan-Auerbach J. (My University, 2006)
The 1999 basaltic eruption of Shishaldin volcano (Alaska, USA) included both Strombolian and Subplinian activity, as well as a "pre-Subplinian" phase interpreted as the local coalescence within a long foam in the conduit. Although few visual observations were made of the eruption, a great deal of information regarding gas velocity, gas flux at the vent and plume height may be inferred by using acoustic recordings of the eruption. By relating acoustic power to gas velocity, a time series of gas velocity is calculated for the Subplinian and pre-Subplinian phases. These time series show trends in gas velocity that are interpreted as plumes or, for those signals lasting only a short time, thermals. The Subplinian phase is shown to be composed of a thermal followed by five plumes with a total expelled gas volume of ≈1.5 × 107 m3. The initiation of the Sub plinian activity is probably related to the arrival of a large overpressurised bubble close to the top of the magma column. A gradual increase in low-frequency (0.01-0.5 Hz) signal prior to this "trigger bubble" may be due to the rise of the bubble in the conduit. This delay corresponds to a reservoir located at ≈3.9 km below the surface, in good agreement with studies on other volcanoes. The presence of two thermal phases is also identified in the middle of the pre-Subplinian phase with a total gas release of ≈4.3 × 106 m3 and ≈ 3.6 × 106 m3. Gas velocity at the vent is found to be ≈82 m.s-1 and ≈90 m.s-1 for the Subplinian plumes and the pre-Subplinian thermals respectively. The agreement is very good between estimates of the gas flux from modelling the plume height and those obtained from acoustic measurements, leading to a new method by which eruption physical parameters may be quantified. Furthermore, direct measurements of gas velocity can be used for better estimates of the SO2 flux released during the eruption. © Springer-Verlag 2005.
Keywords: ACOUSTIC MEASUREMENTS; ALASKA; BASALTIC PLUME; BASALTIC THERMAL; ERUPTION DYNAMICS; SHISHALDIN VOLCANO; SUBDUCTION ZONE